THE EFFECT OF COMMUNICATION AND WORKLOAD ON EMPLOYEE PERFORMANCE WITH WORK SPIRIT AS A MEDIATION VARIABLE - Evelyne Wulan Ayu HW; Adrie Frans Assa; Eka Desy Purnama (CV. Radja Publika, 2025)
In today's modern era, many companies are required to be able to develop and improve human resources so that their performance can increase optimally. Companies need more high-quality human resources to be able to keep up with the tight competition in the beauty industry today. The development of technology and the growth of technology lately as well as the rapidly moving economic sector have an impact on the growth and development of many business worlds. Research on human resources has been widely conducted, especially on communication, workload and work spirit. This study aims to examine the factors that influence employee performance. The method used in this study is descriptive quantitative which discusses several variables that influence employee performance, namely work stress and workload and the role of work conflict as mediation. The formulation of the problem of this study is whether communication, workload and work spirit affect employee performance mediated by work conflict. The purpose of this study is to analyze the effect of communication and workload on employee performance mediated by work spirit. The sample in this study amounted to 179 respondents. Data were collected using a questionnaire on respondents. The data analysis technique used is the Structural Equation Model (SEM) with the SmartPLS Version 3 program. The analysis method uses a measurement model (validity and reliability test), structural model (R-Square), t-test, and mediation effect test. Significant influence between variables on t-Statistics, namely: (1) Communication affects employee performance (2.762), (2) Workload affects employee performance (6.624), (3) Work Spirit affects employee performance (4.879), (4) Communication affects work spirit (6.794), (5) Workload affects Work Spirit (4.554), (6) Work spirit significantly mediates communication on employee performance (3.562), (7) Work spirit significantly mediates partially work load on employee performance (3.930). Suggestions for the company are input for HRD or company owners so that they can complete communication, workload, and work spirit provided by the company to improve employee performance so that employees can work comfortably.